Commentary: Being Hospitable to Teacher Research: A Challenge for the Academy (LEARNing Landscapes, 2015)
In my brief contribution to this edition of LEARNing Landscapes, focusing as it does upon teacher research, integrating action, reflection, and observation, I have chosen to discuss, in particular, the right of teacher research to be recognized and affirmed by the academy in the form of hospitality; a right that is being compromised more and more by the burgeoning neo-liberal culture that dominates so many of our institutions. I argue, in spite of the constraints that are put in its way, that teacher research makes a significant contribution to the development of professional knowledge and, like other aspects of professional practice, is also subject to those parameters that determine quality.
Keywords: teacher reserach; academy; professional practice; quality